Effect of lean-burn combustor outlet flows on nozzle guide vane aerothermal performance: an experimental and computational study - Amend, JE (2024)
Regulatory pressures aimed at reducing NOx and particulate emissions from civil aviation have seen engine manufacturers gravitate towards lean-burn combustor architectures. Compared to their conventional rich-burn counterparts, lean-burn combustors generate significant swirl and alter the temperature distribution at the interface with the high-pressure turbine. We examine the impact of lean-burn on the aerothermal performance of high-pressure nozzle guide vanes (NGV), leveraging engine-scale experiments and simulations.